LINEAR ANNULAR LINEAR ANNULAR LINEAR ANNULAR LINEAR ANNULAR LINEAR ANNULAR LINEAR ANNULAR LINEAR ANNULAR ANTENNAS ARRAY DESIGN BY EVOLUTIONARY ANTENNAS ARRAY DESIGN BY EVOLUTIONARY ANTENNAS ARRAY DESIGN BY EVOLUTIONARY ANTENNAS ARRAY DESIGN BY EVOLUTIONARY - Hichem, Chaker1, Mehadji2 Abri, Badaoui3 Hadjira (university of eloued جامعة الوادي, 2020)
This paper exposes a comparative study that was made between the adaptive particle swarm This paper exposes a comparative study that was made between the adaptive particle swarm This paper exposes a comparative study that was made between the adaptive particle swarm This paper exposes a comparative study that was made between the adaptive particle swarm This paper exposes a comparative study that was made between the adaptive particle swarm This paper exposes a comparative study that was made between the adaptive particle swarm This paper exposes a comparative study that was made between the adaptive particle swarm This paper exposes a comparative study that was made between the adaptive particle swarm This paper exposes a comparative study that was made between the adaptive particle swarm This paper exposes a comparative study that was made between the adaptive particle swarm This paper exposes a comparative study that was made between the adaptive particle swarm This paper exposes a comparative study that was made between the adaptive particle swarm This paper exposes a comparative study that was made between the adaptive particle swarm This paper exposes a comparative study that was made between the adaptive particle swarm This paper exposes a comparative study that was made between the adaptive particle swarm This paper exposes a comparative study that was made between the adaptive particle swarm This paper exposes a comparative study that was made between the adaptive particle swarm This paper exposes a comparative study that was made between the adaptive particle swarm This paper exposes a comparative study that was made between the adaptive particle swarm This paper exposes a comparative study that was made between the adaptive particle swarm This paper exposes a comparative study that was made between the adaptive particle swarm This paper exposes a comparative study that was made between the adaptive particle swarm This paper exposes a comparative study that was made between the adaptive particle swarm This paper exposes a comparative study that was made between the adaptive particle swarm This paper exposes a comparative study that was made between the adaptive particle swarm This paper exposes a comparative study that was made between the adaptive particle swarm This paper exposes a comparative study that was made between the adaptive particle swarm This paper exposes a comparative study that was made between the adaptive particle swarm This paper exposes a comparative study that was made between the adaptive particle swarm This paper exposes a comparative study that was made between the adaptive particle swarm This paper exposes a comparative study that was made between the adaptive particle swarm This paper exposes a comparative study that was made between the adaptive particle swarm This paper exposes a comparative study that was made between the adaptive particle swarm This paper exposes a comparative study that was made between the adaptive particle swarm This paper exposes a comparative study that was made between the adaptive particle swarm This paper exposes a comparative study that was made between the adaptive particle swarm This paper exposes a comparative study that was made between the adaptive particle swarm This paper exposes a comparative study that was made between the adaptive particle swarm This paper exposes a comparative study that was made between the adaptive particle swarm This paper exposes a comparative study that was made between the adaptive particle swarm This paper exposes a comparative study that was made between the adaptive particle swarm optimization (APSO) and the hybrid model genetical swarm optimizer approaches GSO) for optimization (APSO) and the hybrid model genetical swarm optimizer approaches GSO) for optimization (APSO) and the hybrid model genetical swarm optimizer approaches GSO) for optimization (APSO) and the hybrid model genetical swarm optimizer approaches GSO) for optimization (APSO) and the hybrid model genetical swarm optimizer approaches GSO) for optimization (APSO) and the hybrid model genetical swarm optimizer approaches GSO) for optimization (APSO) and the hybrid model genetical swarm optimizer approaches GSO) for optimization (APSO) and the hybrid model genetical swarm optimizer approaches GSO) for optimization (APSO) and the hybrid model genetical swarm optimizer approaches GSO) for optimization (APSO) and the hybrid model genetical swarm optimizer approaches GSO) for optimization (APSO) and the hybrid model genetical swarm optimizer approaches GSO) for optimization (APSO) and the hybrid model genetical swarm optimizer approaches GSO) for optimization (APSO) and the hybrid model genetical swarm optimizer approaches GSO) for optimization (APSO) and the hybrid model genetical swarm optimizer approaches GSO) for optimization (APSO) and the hybrid model genetical swarm optimizer approaches GSO) for optimization (APSO) and the hybrid model genetical swarm optimizer approaches GSO) for optimization (APSO) and the hybrid model genetical swarm optimizer approaches GSO) for optimization (APSO) and the hybrid model genetical swarm optimizer approaches GSO) for optimization (APSO) and the hybrid model genetical swarm optimizer approaches GSO) for optimization (APSO) and the hybrid model genetical swarm optimizer approaches GSO) for optimization (APSO) and the hybrid model genetical swarm optimizer approaches GSO) for optimization (APSO) and the hybrid model genetical swarm optimizer approaches GSO) for optimization (APSO) and the hybrid model genetical swarm optimizer approaches GSO) for optimization (APSO) and the hybrid model genetical swarm optimizer approaches GSO) for optimization (APSO) and the hybrid model genetical swarm optimizer approaches GSO) for optimization (APSO) and the hybrid model genetical swarm optimizer approaches GSO) for optimization (APSO) and the hybrid model genetical swarm optimizer approaches GSO) for optimization (APSO) and the hybrid model genetical swarm optimizer approaches GSO) for optimization (APSO) and the hybrid model genetical swarm optimizer approaches GSO) for optimization (APSO) and the hybrid model genetical swarm optimizer approaches GSO) for optimization (APSO) and the hybrid model genetical swarm optimizer approaches GSO) for optimization (APSO) and the hybrid model genetical swarm optimizer approaches GSO) for optimization (APSO) and the hybrid model genetical swarm optimizer approaches GSO) for optimization (APSO) and the hybrid model genetical swarm optimizer approaches GSO) for optimization (APSO) and the hybrid model genetical swarm optimizer approaches GSO) for optimization (APSO) and the hybrid model genetical swarm optimizer approaches GSO) for optimization (APSO) and the hybrid model genetical swarm optimizer approaches GSO) for optimization (APSO) and the hybrid model genetical swarm optimizer approaches GSO) for optimization (APSO) and the hybrid model genetical swarm optimizer approaches GSO) for optimization (APSO) and the hybrid model genetical swarm optimizer approaches GSO) for optimization (APSO) and the hybrid model genetical swarm optimizer approaches GSO) for the synthesis of 1 the synthesis of 1 the synthesis of 1 the synthesis of 1 the synthesis of 1the synthesis of 1 the synthesis of 1-D equally spaced D equally spacedD equally spaced D equally spaced D equally spaced D equally spaced D equally spacedD equally spacedD equally spaced annular ring antenna arrays for both TMannular ring antenna arrays for both TM annular ring antenna arrays for both TM annular ring antenna arrays for both TM annular ring antenna arrays for both TM annular ring antenna arrays for both TMannular ring antenna arrays for both TM annular ring antenna arrays for both TMannular ring antenna arrays for both TMannular ring antenna arrays for both TMannular ring antenna arrays for both TM annular ring antenna arrays for both TM annular ring antenna arrays for both TM annular ring antenna arrays for both TMannular ring antenna arrays for both TM annular ring antenna arrays for both TM annular ring antenna arrays for both TM 11 and TMand TM and TM 12 modes. The synthesis of 1 modes. The synthesis of 1 modes. The synthesis of 1modes. The synthesis of 1 modes. The synthesis of 1 modes. The synthesis of 1 modes. The synthesis of 1modes. The synthesis of 1 modes. The synthesis of 1modes. The synthesis of 1-D uniform antenna arrays is designed as a mono D uniform antenna arrays is designed as a mono D uniform antenna arrays is designed as a monoD uniform antenna arrays is designed as a monoD uniform antenna arrays is designed as a monoD uniform antenna arrays is designed as a mono D uniform antenna arrays is designed as a monoD uniform antenna arrays is designed as a monoD uniform antenna arrays is designed as a monoD uniform antenna arrays is designed as a mono D uniform antenna arrays is designed as a monoD uniform antenna arrays is designed as a mono D uniform antenna arrays is designed as a mono D uniform antenna arrays is designed as a mono D uniform antenna arrays is designed as a mono D uniform antenna arrays is designed as a monoD uniform antenna arrays is designed as a mono D uniform antenna arrays is designed as a monoD uniform antenna arrays is designed as a monoD uniform antenna arrays is designed as a monoD uniform antenna arrays is designed as a monoD uniform antenna arrays is designed as a monoD uniform antenna arrays is designed as a mono -objective problem. objective problem. objective problem. objective problem. objective problem. objective problem. objective problem. objective problem. The employed optimization techniques are compared in terms of convergence rate and side The employed optimization techniques are compared in terms of convergence rate and side The employed optimization techniques are compared in terms of convergence rate and side The employed optimization techniques are compared in terms of convergence rate and side The employed optimization techniques are compared in terms of convergence rate and side The employed optimization techniques are compared in terms of convergence rate and side The employed optimization techniques are compared in terms of convergence rate and side The employed optimization techniques are compared in terms of convergence rate and side The employed optimization techniques are compared in terms of convergence rate and side The employed optimization techniques are compared in terms of convergence rate and side The employed optimization techniques are compared in terms of convergence rate and side The employed optimization techniques are compared in terms of convergence rate and side The employed optimization techniques are compared in terms of convergence rate and side The employed optimization techniques are compared in terms of convergence rate and side The employed optimization techniques are compared in terms of convergence rate and side The employed optimization techniques are compared in terms of convergence rate and side The employed optimization techniques are compared in terms of convergence rate and side The employed optimization techniques are compared in terms of convergence rate and side The employed optimization techniques are compared in terms of convergence rate and side The employed optimization techniques are compared in terms of convergence rate and side The employed optimization techniques are compared in terms of convergence rate and side The employed optimization techniques are compared in terms of convergence rate and side The employed optimization techniques are compared in terms of convergence rate and side The employed optimization techniques are compared in terms of convergence rate and side The employed optimization techniques are compared in terms of convergence rate and side The employed optimization techniques are compared in terms of convergence rate and side The employed optimization techniques are compared in terms of convergence rate and side The employed optimization techniques are compared in terms of convergence rate and side The employed optimization techniques are compared in terms of convergence rate and side The employed optimization techniques are compared in terms of convergence rate and side The employed optimization techniques are compared in terms of convergence rate and side The employed optimization techniques are compared in terms of convergence rate and side The employed optimization techniques are compared in terms of convergence rate and side The employed optimization techniques are compared in terms of convergence rate and side The employed optimization techniques are compared in terms of convergence rate and side The employed optimization techniques are compared in terms of convergence rate and side The employed optimization techniques are compared in terms of convergence rate and side The employed optimization techniques are compared in terms of convergence rate and side The employed optimization techniques are compared in terms of convergence rate and side The employed optimization techniques are compared in terms of convergence rate and side lobes level reduction. lobes level reduction. lobes level reduction. lobes level reduction. lobes level reduction. lobes level reduction. lobes level reduction. lobes level reduction. lobes level reduction. Several original numerical results are provided to demonstrate the Several original numerical results are provided to demonstrate the Several original numerical results are provided to demonstrate the Several original numerical results are provided to demonstrate the Several original numerical results are provided to demonstrate the Several original numerical results are provided to demonstrate the Several original numerical results are provided to demonstrate the Several original numerical results are provided to demonstrate the Several original numerical results are provided to demonstrate the Several original numerical results are provided to demonstrate the Several original numerical results are provided to demonstrate the Several original numerical results are provided to demonstrate the Several original numerical results are provided to demonstrate the Several original numerical results are provided to demonstrate the Several original numerical results are provided to demonstrate the Several original numerical results are provided to demonstrate the Several original numerical results are provided to demonstrate the Several original numerical results are provided to demonstrate the Several original numerical results are provided to demonstrate the Several original numerical results are provided to demonstrate the Several original numerical results are provided to demonstrate the Several original numerical results are provided to demonstrate the Several original numerical results are provided to demonstrate the Several original numerical results are provided to demonstrate the Several original numerical results are provided to demonstrate the Several original numerical results are provided to demonstrate the Several original numerical results are provided to demonstrate the Several original numerical results are provided to demonstrate the Several original numerical results are provided to demonstrate the Several original numerical results are provided to demonstrate the Several original numerical results are provided to demonstrate the performance of the proposed techniques. The results reveal that suggested array antenna performance of the proposed techniques. The results reveal that suggested array antenna performance of the proposed techniques. The results reveal that suggested array antenna performance of the proposed techniques. The results reveal that suggested array antenna performance of the proposed techniques. The results reveal that suggested array antenna performance of the proposed techniques. The results reveal that suggested array antenna performance of the proposed techniques. The results reveal that suggested array antenna performance of the proposed techniques. The results reveal that suggested array antenna performance of the proposed techniques. The results reveal that suggested array antenna performance of the proposed techniques. The results reveal that suggested array antenna performance of the proposed techniques. The results reveal that suggested array antenna performance of the proposed techniques. The results reveal that suggested array antenna performance of the proposed techniques. The results reveal that suggested array antenna performance of the proposed techniques. The results reveal that suggested array antenna performance of the proposed techniques. The results reveal that suggested array antenna performance of the proposed techniques. The results reveal that suggested array antenna performance of the proposed techniques. The results reveal that suggested array antenna performance of the proposed techniques. The results reveal that suggested array antenna performance of the proposed techniques. The results reveal that suggested array antenna performance of the proposed techniques. The results reveal that suggested array antenna performance of the proposed techniques. The results reveal that suggested array antenna performance of the proposed techniques. The results reveal that suggested array antenna performance of the proposed techniques. The results reveal that suggested array antenna performance of the proposed techniques. The results reveal that suggested array antenna performance of the proposed techniques. The results reveal that suggested array antenna performance of the proposed techniques. The results reveal that suggested array antenna performance of the proposed techniques. The results reveal that suggested array antenna performance of the proposed techniques. The results reveal that suggested array antenna performance of the proposed techniques. The results reveal that suggested array antenna performance of the proposed techniques. The results reveal that suggested array antenna performance of the proposed techniques. The results reveal that suggested array antenna performance of the proposed techniques. The results reveal that suggested array antenna performance of the proposed techniques. The results reveal that suggested array antenna performance of the proposed techniques. The results reveal that suggested array antenna performance of the proposed techniques. The results reveal that suggested array antenna performance of the proposed techniques. The results reveal that suggested array antenna performance of the proposed techniques. The results reveal that suggested array antenna performance of the proposed techniques. The results reveal that suggested array antenna synthesis approach using genetical swarm optimizer outperforms the adaptive particle synthesis approach using genetical swarm optimizer outperforms the adaptive particle synthesis approach using genetical swarm optimizer outperforms the adaptive particle synthesis approach using genetical swarm optimizer outperforms the adaptive particle synthesis approach using genetical swarm optimizer outperforms the adaptive particle synthesis approach using genetical swarm optimizer outperforms the adaptive particle synthesis approach using genetical swarm optimizer outperforms the adaptive particle synthesis approach using genetical swarm optimizer outperforms the adaptive particle synthesis approach using genetical swarm optimizer outperforms the adaptive particle synthesis approach using genetical swarm optimizer outperforms the adaptive particle synthesis approach using genetical swarm optimizer outperforms the adaptive particle synthesis approach using genetical swarm optimizer outperforms the adaptive particle synthesis approach using genetical swarm optimizer outperforms the adaptive particle synthesis approach using genetical swarm optimizer outperforms the adaptive particle synthesis approach using genetical swarm optimizer outperforms the adaptive particle synthesis approach using genetical swarm optimizer outperforms the adaptive particle synthesis approach using genetical swarm optimizer outperforms the adaptive particle synthesis approach using genetical swarm optimizer outperforms the adaptive particle synthesis approach using genetical swarm optimizer outperforms the adaptive particle synthesis approach using genetical swarm optimizer outperforms the adaptive particle synthesis approach using genetical swarm optimizer outperforms the adaptive particle synthesis approach using genetical swarm optimizer outperforms the adaptive particle synthesis approach using genetical swarm optimizer outperforms the adaptive particle synthesis approach using genetical swarm optimizer outperforms the adaptive particle synthesis approach using genetical swarm optimizer outperforms the adaptive particle synthesis approach using genetical swarm optimizer outperforms the adaptive particle synthesis approach using genetical swarm optimizer outperforms the adaptive particle synthesis approach using genetical swarm optimizer outperforms the adaptive particle synthesis approach using genetical swarm optimizer outperforms the adaptive particle synthesis approach using genetical swarm optimizer outperforms the adaptive particle synthesis approach using genetical swarm optimizer outperforms the adaptive particle synthesis approach using genetical swarm optimizer outperforms the adaptive particle synthesis approach using genetical swarm optimizer outperforms the adaptive particle synthesis approach using genetical swarm optimizer outperforms the adaptive particle synthesis approach using genetical swarm optimizer outperforms the adaptive particle synthesis approach using genetical swarm optimizer outperforms the adaptive particle synthesis approach using genetical swarm optimizer outperforms the adaptive particle synthesis approach using genetical swarm optimizer outperforms the adaptive particle synthesis approach using genetical swarm optimizer outperforms the adaptive particle synthesis approach using genetical swarm optimizer outperforms the adaptive particle synthesis approach using genetical swarm optimizer outperforms the adaptive particle synthesis approach using genetical swarm optimizer outperforms the adaptive particle synthesis
artical
Keywords: Ring microstrip antenna; Linear Antenna Arrays; Genetical swarm oRing microstrip antenna; Linear Antenna Arrays; Genetical swarm o Ring microstrip antenna; Linear Antenna Arrays; Genetical swarm o Ring microstrip antenna; Linear Antenna Arrays; Genetical swarm oRing microstrip antenna; Linear Antenna Arrays; Genetical swarm o Ring microstrip antenna; Linear Antenna Arrays; Genetical swarm oRing microstrip antenna; Linear Antenna Arrays; Genetical swarm o Ring microstrip antenna; Linear Antenna Arrays; Genetical swarm o Ring microstrip antenna; Linear Antenna Arrays; Genetical swarm o Ring microstrip antenna; Linear Antenna Arrays; Genetical swarm oRing microstrip antenna; Linear Antenna Arrays; Genetical swarm o Ring microstrip antenna; Linear Antenna Arrays; Genetical swarm o Ring microstrip antenna; Linear Antenna Arrays; Genetical swarm oRing microstrip antenna; Linear Antenna Arrays; Genetical swarm o Ring microstrip antenna; Linear Antenna Arrays; Genetical swarm oRing microstrip antenna; Linear Antenna Arrays; Genetical swarm o Ring microstrip antenna; Linear Antenna Arrays; Genetical swarm oRing microstrip antenna; Linear Antenna Arrays; Genetical swarm oRing